2004
DOI: 10.1248/cpb.52.1175
|View full text |Cite
|
Sign up to set email alerts
|

A New Dimeric Carbazole Alkaloid from Glycosmis stenocarpa Roots

Abstract: The genus Glycosmis, family Rutaceae, is a rich source of alkaloids, including those of the quinolone, quinazoline, furoquinoline, acridone, sulphur-containing amides and carbazole types.1,2) Carbazole alkaloids were isolated from the seeds 3) and the roots 4,5) of G. pentaphylla, from the bark of G. mauritiana 6) and G. rupestris, 7) and from the roots of G. arborea. 8) Carbazole alkaloids have also been found in other Rutaceous genera, e.g., Micromelum, Murraya, and Clausena. From two genera, Murraya and Cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 22 publications
(29 reference statements)
1
25
0
Order By: Relevance
“…3.96 (s) 56.9 (q) C ( 3 ') genus. Bisisomahanine isolated from G. stenocarpa represented the first dimeric prenylated pyranocarbazole alkaloid with a 1,1'-linkage [16]. In the present study, compounds 2 and 3 which present a 1,1'-linkage between two carbazole moieties, were isolated from G. pentaphylla for the first time.…”
mentioning
confidence: 62%
“…3.96 (s) 56.9 (q) C ( 3 ') genus. Bisisomahanine isolated from G. stenocarpa represented the first dimeric prenylated pyranocarbazole alkaloid with a 1,1'-linkage [16]. In the present study, compounds 2 and 3 which present a 1,1'-linkage between two carbazole moieties, were isolated from G. pentaphylla for the first time.…”
mentioning
confidence: 62%
“…Since the first report of a carbazole alkaloid, murrayanine, from the stem bark of Murraya koenigii [15], a number of carbazole alkaloids have been isolated from this plant [16][17][18][19][20] and other plants [13,21]. Although there are many carbazole alkaloid derivatives that have special ability to scavenge reactive oxygen species-free radicals, such as hydroxyl radicals, superoxide radicals, or hypochlorous acid, and to influence processes involving free-radical injury [22,23], they have also been found to inhibit lipid peroxidation and to possess vasorelaxant [24][25][26] and anti-inflammatory/antioxidant activity [20].…”
Section: Resultsmentioning
confidence: 99%
“…Bisisomahanine (8), ah omocoupling product of pyrayafoline D, was isolatedi n 2004 by Cuong et al from the roots of Glycosmis stenocarpa and reported to be optically active (½a 20 D = À13.1, c = 0.25, CHCl 3 ). [68] However,t he authors did not assign the absolute configuration. Treatment of pyrayafoline C( 23)a nd D( 24)w ith di-tert-butyl peroxide afforded the corresponding dimers 7 and 8 in 85 %a nd 64 %y ield, respectively ( Table 3).…”
Section: Introductionmentioning
confidence: 99%